Closing the loop: the relationship between instructor-reflective practice and students' satisfaction and quality outcomes - Scott, S.; Issa, Tomayess; Issa, Theodora (Common Ground, 2008)
This research outlines a case study involving over 450 students whereby 'closing the loop' between using student feedback to inform instructor-reflection and development led to improved student satisfaction and quality of projects. This research was a 5-year longitudinal study and reports on the results of an action-learning methodology informed by systematic professional development. The instructors were within the business technology discipline and used students' feedback to make ongoing developments to the curriculum, and teaching and assessment practices. Sustained action research incorporating a critical friend to facilitate reflection and problem-solving was adopted. A combination of methods for collecting data was employed; for example, student feedback questionnaires, student meetings, and instructor/professional developer journaling. The outcomes included significantly higher scores in the student feedback instrument in comparison to the school average; and increases in student satisfaction ratings and responses across the years. The overall quality of the final project also increased across subsequent years. For the academics outcomes included increased feelings of empowerment with making sound teaching decisions; increased satisfaction in observing and supporting good teaching; developing cognitively challenging assessments that were more explicit and well structured; and course work and assessments that embedded team-working and critical thinking skills.